2011
DOI: 10.1038/onc.2011.249
|View full text |Cite
|
Sign up to set email alerts
|

MT1-MMP protects breast carcinoma cells against type I collagen-induced apoptosis

Abstract: As invading breast carcinoma cells breach their underlying basement membrane, they become confronted with a dense three-dimensional reactive stroma dominated by type I collagen. To develop metastatic capabilities, invading tumor cells must acquire the capacity to negotiate this novel microenvironment. Collagen influences the fate of epithelial cells by inducing apoptosis. However, the mechanisms used by invading tumor cells to evade collagen-induced apoptosis remain to be defined. We demonstrate that membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 63 publications
(74 reference statements)
7
74
2
Order By: Relevance
“…1E), and adding doxycycline to the growth medium switched off ADAM12 expression (MCF7-A12Dcyt+dox). In contrast to earlier publications (Deryugina et al, 2000;Figueira et al, 2009;Maquoi et al, 2012), we were able to detect equal levels of MMP-14 under all three experimental conditions (Fig. 1E).…”
Section: Mmp-14 Recruitment To the Tumor Cell Surface Is Stimulated Bcontrasting
confidence: 99%
See 2 more Smart Citations
“…1E), and adding doxycycline to the growth medium switched off ADAM12 expression (MCF7-A12Dcyt+dox). In contrast to earlier publications (Deryugina et al, 2000;Figueira et al, 2009;Maquoi et al, 2012), we were able to detect equal levels of MMP-14 under all three experimental conditions (Fig. 1E).…”
Section: Mmp-14 Recruitment To the Tumor Cell Surface Is Stimulated Bcontrasting
confidence: 99%
“…MMP-14 is a classical transmembrane metalloproteinase and, like ADAM12, it is upregulated in human cancer (Egeblad and Werb, 2002;Figueira et al, 2009;Jiang et al, 2006;Seiki, 2003;Strongin, 2010) and accelerates tumor progression in mouse models of cancer (Fröhlich et al, 2011;Kveiborg et al, 2005;Maquoi et al, 2012;Perentes et al, 2011;Roy et al, 2011). MMP-14 degrades extracellular matrix components (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that MT1-MMP protects cancer cells from apoptosis induced by collagen gel culture [21]. HSC-4 cells used here express mutant form of p53-R248Q [22] and lack the expression of PTEN (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MT1-MMP (MMP14) has emerged as an important collagenase that cancer cells use to degrade and invade in a collagen-rich environment [9,10]. While poorly invasive breast adenocarcinoma cells undergo apoptosis when confronted with a collagen-rich environment, the production of MT1-MMP endows these cells with the capacity to escape from collagen-induced apoptosis [11]. The localized activity of MT1-MMP helps tumour cells to overcome higher collagen density found in some peritumoural stroma [12].…”
Section: Introductionmentioning
confidence: 99%